Fatigue Alters Landing Shock Attenuation During a Single-Leg Vertical Drop Jump - Tamura, Akihiro (Orthop J Sports Med, 2016)
BACKGROUND: Landings in fatigue conditions are considered to be one of the factors that cause noncontact anterior cruciate ligament (ACL) injury. Additionally, it is known that fatigue alters lower extremity landing strategies and decreases the ability to attenuate shock during landing. PURPOSE: To determine characteristics of knee kinematics and shock attenuation during the landing phase of a single-leg vertical drop jump in a fatigued condition. The hypothesis was that knee kinematics during the landing phase of a single-leg vertical drop jump would demonstrate a significant difference between before and after fatigue. STUDY DESIGN: Controlled laboratory study. METHODS: Thirty-four college females participated in this experiment. They were randomly assigned to either the fatigue (n = 17) or control group (n = 17). The fatigue group performed the single-leg vertical drop jump before and after the fatigue protocol, which was performed on a bike ergometer. Knee kinematics data were obtained from the 3-dimensional motion analysis system. The ratio of each variable (%) was calculated, comparing the pre- to postfatigue protocol. Unpaired t tests were used to compare changes in kinematic variables between the fatigue-induced group and control group. RESULTS: Peak knee flexion angular velocity increased significantly in the fatigue group (106.1% ± 8.0%) in comparison with the control group (100.7% ± 6.6%) (P < .05). However, peak knee flexion angle and acceleration had no differences between each group. Peak knee adduction/abduction angle, velocity, and acceleration also had no differences between each group. CONCLUSION: Fatigue decreased the ability to attenuate shock by increasing angular velocity in the direction of knee flexion during single-leg drop jump landing. These findings indicate the need to evaluate the ability to attenuate shock by measuring knee flexion angular velocity when fatigue is considered. CLINICAL RELEVANCE: Measuring knee angular velocity during landings might be an important evaluation parameter in the consideration of the knee injury prevention.